مدى استخدام مدقق الحسابات الخارجي لمعيار التدقيق الدولي/570/ دراسة ميدانية في البيئة السورية - الأمين, ماهر (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تعتبر مهنة تدقيق الحسابات من المهن الهامة في المجتمع لما تقدمه من خدمات مختلفة تستفيد منها أطراف عديدة فيه،وذلك من خلال الرأي الفني المهني المحايد المتمثل بتقرير المدقق الخارجي عن القوائم المالية التي قام بتدقيقها.ولذلك فهو مسؤول أمام تلك الأطراف قانونياً ومهنياً وأدبياً،وعليه العمل وفق معايير العمل المهني وقواعد وآداب السلوك المهني. وفي سورية يعمل المدقق في البيئة التي نظمت فيها مهنة المحاسبة والتدقيق وفق قانون مجلس المحاسبة والتدقيق رقم /33/ الصادر عام 2009.يهدف البحث إلى بيان مدى استخدام مدققي الحسابات في سورية لمعيار التدقيق الدولي رقم/570/المتعلق باستمرارية المنشأة في عملها،والتعرف على وجود شك جوهري في قدرتها على الاستمرار,ومدى ملاءمة مؤشرات الشك التي يستدل بها المدققون على قدرة المنشأة على الاستمرار مع المؤشرات المحددة في المعيار المذكور.كما ويهدف الى التعرف على إجراءات التدقيق الإضافية التي يتبعها المدققون في حال وجود أحداث أو ظروف قد تؤثر على استمرارية المنشأة,ومدى ملاءمة هذه الإجراءات مع الإجراءات المحددة في المعيار المذكور.توصل البحث إلى أن من أهم المؤشرات التي تساعد مدققي الحسابات محل الدراسة في تقييم الاستمرارية عند وجود شك جوهري في قدرة المنشأة محل التدقيق على الاستمرار:وجود خسائر مالية متكررة،زيادة المطلوبات المتداولة على الموجودات المتداولة،تأخر توزيع الأرباح لعدد من السنوات.وأن من أهم إجراءات التدقيق الإضافية التي يقوم بها المدققون عندئذ تحليل ومناقشة التدفقات النقدية والأرباح مع الإدارة.The auditing profession is held to be important in society, due to the various services it provides for many parties ,through the vocational technical and neutral report of the external auditor of concerned financial data.Therefore ,he will be responsible towards those parties legally, professionally and morally ,and must act in accordance with professional work level (standards),and the rules and ethics of professional conduct.In Syria ,the checker works in the field of accounting and auditing ,according to Act no./33/ of 2009,issued by auditing and accounting council .The research aims to show the extent of the use of auditors in Syria of the international auditing standard no./570/related to the continuity of the establishment in its work ,and the presence of essential doubt in its capacity to continue and the suitability of these indicators with specified indicators in the above cited standard.This research work also aims to identify the additional audit procedures followed by the auditors in the event of the presence of certain circumstances that may affect the continuity of the business, and the suitability of these specific actions mentioned in the standard.The research found that the most important indicators that help auditors assess the continuity of the establishment, in case there is significant doubt about the ability of the establishment under consideration to continue, are as follows: the presence of frequent financial losses, an increase in current liabilities to current assets, delayed distribution of profits for a number of years. Thus, The most important additional audit procedures carried out by the auditors will be the analysis and discussion of cash flow and profits with the management.